Analysis of Productive Waqf Transformation and Cost Efficiency on Health Infrastructure Development in Bogor Regency - Judijanto, Loso; Muhtadi, Muhamad Ammar; Lesmana, Tera (West Science Social and Humanities Studies, 2024)
This study explores the transformation of traditional waqf into productive waqf and its role in enhancing cost efficiency for health infrastructure development in Bogor Regency. Using a qualitative approach, the study draws on data from four key informants and document analysis, with findings analyzed through NVivo software. The research highlights how innovative waqf management strategies, such as leasing waqf land and reinvesting revenues, have contributed to sustainable financing of healthcare projects. Despite its potential, challenges such as regulatory constraints, limited management capacity, and cultural perceptions of waqf hinder its full implementation. The study emphasizes the need for regulatory reforms, capacity-building initiatives, and community engagement to optimize the use of productive waqf in public infrastructure. These findings provide valuable insights for policymakers, waqf institutions, and healthcare planners in leveraging Islamic financial instruments for sustainable development.